Eating patterns in the Brazilian Longitudinal Study of Adult Health (ELSA-Brasil): an exploratory analysis - Letícia de Oliveira Cardoso; Marilia Sá Carvalho; Oswaldo Gonçalves Cruz; Cristiane Melere; Vivian Cristine Luft; Maria del Carmen Bisi Molina; Carolina Perim de Faria; Isabela M. Benseñor; Sheila Maria Alvim Matos; Maria de Jesus Mendes da Fonseca; Rosane Harter Griep; Dóra Chor (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2016)
Abstract: The food consumption of 15,071 public employees was analyzed in six Brazilian cities participating in the baseline for Brazilian Longitudinal Study of Adult Health (ELSA-Brasil, 2008-2010) with the aim of identifying eating patterns and their relationship to socio-demographic variables. Multiple correspondence and cluster analysis were applied. Four patterns were identified, with their respective frequencies: "traditional" (48%); "fruits and vegetables" (25%); "pastry shop" (24%); and "diet/light" (5%) The "traditional" and "pastry shop" patterns were more frequent among men, younger individuals, and those with less schooling. "Fruits and vegetables" and "diet/light" were more frequent in women, older individuals, and those with more schooling. Our findings show the inclusion of new items in the "traditional" pattern and the appearance of the "low sugar/low fat" pattern among the eating habits of Brazilian workers, and signal socio-demographic and regional differences.